KERANGKA KERJA KETANGGUHAN PARIWISATA DUNIA PASCA COVID-19: Sebuah Kajian Dokumen - I Ketut Budarma; Ni Made Rai Erawati (Universitas Triatma Mulya, 2022)
The Covid-19 pandemic has had a negative impact on world tourism, this incident has prompted researchers to conduct studies related to the reorientation of tourism development after the Covid-19 pandemic. The researchers conducted various reviews so that tourism in the future would be more resilient. Post-covid-19 tourism resilience needs to be carried out in an integrated manner through government policies, research and innovation, technological interventions, consumer and employee confidence and community involvement. A reorientation of post-covid-19 tourism development that is resilient, carried out with an inclusive approach, can make tourism one of the new global economic orders, characterized by safety and comfort, sustainability, stakeholder involvement and integration of tourism with traditional sectors such as agriculture, culture, animal husbandry and retail. Post-pandemic tourism development is often also called new normal tourism. This research examines the policies and conventions of the world tourism agencies related to the development of a more resilient tourism industry in the future. This research found that a more resilient tourism mapping in the future is global, inclusive and fair, all stakeholders have to take responsibility for the sake of the business sustainability.